Fake and Reality of Our World - Sergey N. Il’chenko (Гуманитарный вектор, 2021)
The article is a review of books by two foreign authors translated into Russian and published in 2020. The first of these is a popular science publication by Dutch fake researcher Annemarie Bohn. She uses the material of her national and foreign media to tell about the history of the emergence and nature of such a phenomenon of modern media culture as fake. At the same time, the author shows some bias in assessing a number of situations that have developed in recent years in the global information space. Nevertheless, this publication is quite adequate educational in nature, allowing you “to enter the topic” for those who want to learn more about fakes in journalism for the first time. The name of the author of the second peer-reviewed publication is already known to Russian readers. Robert Kiyosaki’s previous book Rich Dad Poor Dad, a world bestseller, was translated and published in Russia. In the new work, the Japanese-American continues a deep and comprehensive analysis of the modern American financial and monetary system. The author uses the concepts of fake and fake manipulation to expose, from his point of view, the imperfections of the existing US financial system.